Patterns of Value Inculcation to Build an Anti-Corruption Culture in the Family Environment as a Preventive Actions in the Globalization Era - Setyowati, Rr Nanik; Sarmini,; Sukma, Perdana P.; El Rizaq, Agung Dwi Bahtiar (Advances in Social Sciences Research Journal, 2023)
Building an anti-corruption culture is a shared responsibility, family, community, parents and schools. The synergy between the roles of parents and schools is social capital to build an anti-corruption culture for the younger generation. This study focuses on analyzing parental constructs regarding urgency, role, efforts that have been made, and values inculcated in building an anti-corruption culture for the younger generation. This study used a descriptive quantitative approach which was conducted through a survey of 180 guardians of Junior High school students in Sidoarjo Regency. The results of this study indicate that parents have carried out anti-corruption education through various approaches emphasizing honesty as the main value that is inculcated from an early age. The next finding regarding understanding the values that build an anti-corruption culture has not been fully understood by parents. Parents do not have the right model in inculcating anti-corruption values. This study recommends that anti-corruption education be carried out collaboratively between schools and parents.